The hydrating effects of hypertonic, isotonic and hypotonic sports drinks and waters on central hydration during continuous exercise: a systematic meta-analysis and perspective - Rowlands, D. S.; Kopetschny, B. H.; Badenhorst, C. E. (Sports Medicine, 2022)
Background: Body-fluid loss during prolonged continuous exercise can impair cardiovascular function, harming performance. Delta percent plasma volume (dPV) represents the change in central and circulatory body-water volume and therefore hydration during exercise; however, the effect of carbohydrate-electrolyte drinks and water on the dPV response is unclear. Objective: To determine by meta-analysis the effects of ingested hypertonic (> 300 mOsmol kg-1), isotonic (275-300 mOsmol kg-1) and hypotonic (< 275 mOsmol kg-1) drinks containing carbohydrate and electrolyte ([Na+] < 50 mmol L-1), and non-carbohydrate drinks/water (< 40 mOsmol kg-1) on dPV during continuous exercise. Methods: A systematic review produced 28 qualifying studies and 68 drink treatment effects. Random-effects meta-analyses with repeated measures provided estimates of effects and probability of superiority (p+) during 0-180 min of exercise, adjusted for drink osmolality, ingestion rate, metabolic rate and a weakly informative Bayesian prior. Results: Mean drink effects on dPV were: hypertonic - 7.4% [90% compatibility limits (CL) - 8.5, - 6.3], isotonic - 8.7% (90% CL - 10.1, - 7.4), hypotonic - 6.3% (90% CL - 7.4, - 5.3) and water - 7.5% (90% CL - 8.5, - 6.4). Posterior contrast estimates relative to the smallest important effect (dPV = 0.75%) were: hypertonic-isotonic 1.2% (90% CL - 0.1, 2.6; p+ = 0.74), hypotonic-isotonic 2.3% (90% CL 1.1, 3.5; p+ = 0.984), water-isotonic 1.3% (90% CL 0.0, 2.5; p+ = 0.76), hypotonic-hypertonic 1.1% (90% CL 0.1, 2.1; p+ = 0.71), hypertonic-water 0.1% (90% CL - 0.8, 1.0; p+ = 0.12) and hypotonic-water 1.1% (90% CL 0.1, 2.0; p+ = 0.72). Thus, hypotonic drinks were very likely superior to isotonic and likely superior to hypertonic and water. Metabolic rate, ingestion rate, carbohydrate characteristics and electrolyte concentration were generally substantial modifiers of dPV. Conclusion: Hypotonic carbohydrate-electrolyte drinks ingested continuously during exercise provide the greatest benefit to hydration.